Application of Self-propagating High-temperature Synthesis to High-current Electronics; The International Journal of Self-Propagating High-Temperature Synthesis; Vol. 13, № 2 - Dolmatov O. Yu. Oleg Yurevich (2004, 2004)
The production of materials applicable to manufacturing electron emitters with preset properties using the SHS method was considered. The conditions required for the process to take place in a reactionable mixture were analyzed taking into account the thermodynamically calculated adiabatic temperature. The possibility of producing cathodic materials was demonstrated experimentally. The material phase composition was studied. The synthesis products were tested on an high-current accelerator. The advantages of the SHS cathodes over conventional cathodes were discussed.